Голгофа. Благие намерения: повесть - Лиханов Альберт (2010)
Экземпляры: Селтинская районная библиотека (к/х) (20101231) / Инвентарный номер: 197353 / Цена: 206.25 / Авт.знак: Л 65 / ГРНТИ: 17.82.93 / ББК: 84(2=411.2)6